Breaking the resolution limits of 3D bioprinting: future opportunities and present challenges. Issue 5 (May 2023) - Zandrini, Tommaso; Florczak, Sammy; Levato, Riccardo; Ovsianikov, Aleksandr
Abstract: Bioprinting aims to produce 3D structures from which embedded cells can receive mechanical and chemical stimuli that influence their behavior, direct their organization and migration, and promote differentiation, in a similar way to what happens within the native extracellular matrix. However, limited spatial resolution has been a bottleneck for conventional 3D bioprinting approaches. Reproducing fine features at the cellular scale, while maintaining a reasonable printing volume, is necessary to enable the biofabrication of more complex and functional tissue and organ models. In this opinion article we recount the emergence of, and discuss the most promising, high-definition (HD) bioprinting techniques to achieve this goal, discussing which obstacles remain to be overcome, and which applications are envisioned in the tissue engineering field. Highlights: High-definition (HD) bioprinting enables spatial resolution on a cellular and subcellular level in 3D, allowing reproduction of key features of the cellular microenvironment at a scale not achievable with conventional bioprinting techniques, and allowing control of material properties, geometry, and chemical and physical properties of cell-containing constructs. Light-based, precision jetting, and electrohydrodynamic technologies can already achieve such resolution, and will be increasingly applied to engineer disease models, organ-on-a-chip devices, and implantable microscaffolds with high complexity. Standing challenges include preserving microscale and submicroscale resolution while enabling high-throughput and volumetric construct bioprinting, streamlined multimaterial processing, and the development of new functional (bio)inks and (bio)resins.